Wnt Pathway Activation in Long Term Remnant Rat Model. (5th June 2014) - Banon-Maneus, E.; Rovira, J.; Ramirez-Bajo, M. J.; Moya-Rull, D.; Hierro-Garcia, N.; Takenaka, S.; Diekmann, F.; Eickelberg, O.; Königshoff, M.; Campistol, J. M.
Abstract : Progression of chronic kidney disease (CKD) is characterized by deposition of extracellular matrix. This is an irreversible process that leads to tubulointerstitial fibrosis and finally loss of kidney function. Wnt/ β -catenin pathway was reported to be aberrantly activated in the progressive damage associated with chronic organ failure. Extensive renal ablation is an experimental model widely used to gain insight into the mechanisms responsible for the development of CKD, but it was not evaluated for Wnt/ β -catenin pathway. This study aimed to elucidate if the rat 5/6 renal mass reduction model (RMR) is a good model for the Wnt/ β -catenin activation and possible next modulation. RMR model was evaluated at 12 and 18 weeks after the surgery, when CKD is close to end-stage kidney disease demonstrated by molecular and histological studies. Wnt pathway components were analyzed at mRNA and protein level. Our results demonstrate that Wnt pathway is active by increase of β -catenin at mRNA level and nuclear translocation in tubular epithelium as well as some target genes. These results validate the RMR model for future modulation of Wnt pathway, starting at shorter time after the surgery.